Effects of Teaching Method Based on the Science Writing Heuristic Approach on Science Process Skills - (:unkn) unknown (HACETTEPE UNIV, 2015)
The purpose of this study is to find out the effects of teaching method based on science writing heuristic approach on science process skills. Science Writing Heuristic (SWH) which is an inquiry based approach was developed by Keys, Hand, Prain and Collins (1999). The sampling of our study was comprised of the students from a primary public school in Yalova. The students were 7th graders in the academic year of 2010-2011. A total of 65 students (the experimental group 33 and the control group 32) participated in our study. The Science process skills test developed by Aydogdu (2006) and whose reliability was 0,81 used as a data instrument in this study. The experimental group performed laboratory activities in science and Technology lessons through science writing heuristics, the control group performed laboratory activities through traditional approach. After the implementation there was a significant difference (p=0,05) between the experimental and the control groups in favor of the experimental group in terms of science process skills such as identifying variables, identifying and stating hypotheses, operationally defining and investigations designing.
Keywords: science writing heuristic approach; inquiry; science process skills; ACHIEVEMENT